Dmitri Shostakovich: a work of virtuosity or a profitable misfortune? - Germán José Medina-Rincón; Sofía Martínez-Gil; Luis Octavio Tierradentro-García; Eduardo Esteban Orrego-González; Juan Sebastián Botero-Meneses (Arquivos de Neuro-Psiquiatria)
Abstract Dmitri Shostakovich was one of the greatest composers of 20th century, famous for his piano and violin compositions. One of the compositions, the 5th symphony, is arguably his greatest work, which brought him back to the grace of the Soviet authorities in a moment of a political crisis in Russia. Among the experts, there is a theory which supports that Shostakovich’s talent was due to a traumatic brain injury involving a shrapnel. Moreover, he might have suffered from a neurodegenerative process throughout his life. In this paper, we intend to discuss these viewpoints.